2019
DOI: 10.1039/c8gc02994f
|View full text |Cite
|
Sign up to set email alerts
|

Combining steam distillation with microwave-assisted pyrolysis to maximise direct production of levoglucosenone from agricultural wastes

Abstract: The favourable impact of using a wet waste stream of agricultural residues in a biorefinery was studied through a combination of pyrolysis and self-induced steam distillation of hemicellulose depleted barley straw.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Dihydrolevoglucosenone, more commonly known as Cyrene, is a novel green solvent produced from cellulose in a two-step process. A good hydrogen bond accepting capacity, owing to its one carbonyl and two ether groups, makes Cyrene a polar yet aprotic solvent, with properties similar to other aprotic solvents such as N -methyl-2-pyrrolidone (NMP). Due to its biodegradability and the abundance of its precursor, Cyrene has attracted considerable interest, with studies showing it to be an excellent medium for a wide variety of chemical reactions, including graphene processing …”
Section: Introductionmentioning
confidence: 99%
“…Dihydrolevoglucosenone, more commonly known as Cyrene, is a novel green solvent produced from cellulose in a two-step process. A good hydrogen bond accepting capacity, owing to its one carbonyl and two ether groups, makes Cyrene a polar yet aprotic solvent, with properties similar to other aprotic solvents such as N -methyl-2-pyrrolidone (NMP). Due to its biodegradability and the abundance of its precursor, Cyrene has attracted considerable interest, with studies showing it to be an excellent medium for a wide variety of chemical reactions, including graphene processing …”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the sequence of reactions enabled the production of bioethanol, LGO, and lignin derivatives. The same research group confirmed a selective LGO production from the microwave-assisted pyrolysis of hemicellulose-depleted biomass from barley straw. In the study, the vaporization of water in the wet sample accompanied the isolation of LGO from the pyrolyzing solid under microwave irradiation.…”
Section: Feedstock Optionsmentioning
confidence: 77%
“…The material was processed at a high temperature and high humidity gas (Tian et al., 2021). Currently, the hot steam generated by microwaves is widely used in food processing, biomaterial drying, and heat treatment (Bouxin et al., 2019; Cao et al., 2018). For example, Xu et al.…”
Section: Research Progress In Microwave Heating With Steam As Carriermentioning
confidence: 99%